Purple light excited orange fluorescent powder as well as preparation method and application thereof

By preparing Zn4CdS5 phosphor, the problems of low luminescence efficiency, insufficient color purity and poor stability in the prior art are solved, and the purple-light-excited orange phosphor with high efficiency emission and strong stability are achieved, which is suitable for lighting devices.

CN120248870AActive Publication Date: 2025-07-04SHANGHAI INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510272404.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-07-04
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

During the synthesis process, existing sulfide phosphors have problems such as limited luminescence efficiency, insufficient color purity, poor material stability and complex preparation process, which are difficult to meet the needs of modern display and lighting technologies.

Method used

Using the chemical formula of Zn4CdS5, the Zn and Cd-containing compounds were mixed and then calcined in a vacuum quartz tube in stages, and the temperature and time were controlled to prepare a purple-excited orange phosphor.

Benefits of technology

The prepared orange phosphor has strong emission intensity and physical and chemical stability under the excitation of purple light, and can match commercial purple light LED chips, which is suitable for lighting devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120248870A_ABST
    Figure CN120248870A_ABST
Patent Text Reader

Abstract

The invention relates to purple light excited orange fluorescent powder as well as a preparation method and application thereof. The chemical formula of the orange fluorescent powder is Zn4CdS5. The preparation method comprises the following steps: grinding and uniformly mixing a Zn-containing compound and a Cd-containing compound, sealing in a vacuum quartz tube, calcining, and cooling to obtain the orange fluorescent powder, wherein the Zn-containing compound and the Cd-containing compound contain an S element. Compared with the prior art, the orange fluorescent powder prepared by the invention has the advantages of higher emission intensity and stable physical and chemical properties, and can be widely matched with commercial purple light LED chips.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of phosphor preparation, and particularly to a purple-light-excited orange phosphor, its preparation method and application. Background Art

[0002] With the rapid development of modern display technologies, optoelectronic devices, and lighting technologies, orange-red light-emitting phosphors have attracted increasing attention due to their important roles in displays and lighting. Sulfide-based phosphors have become a promising research direction due to their high quantum efficiency, good thermal stability, and ability to withstand environmental changes. However, traditional sulfide phosphors still suffer from problems such as limited luminous efficiency, insufficient color purity, poor material stability, and complex preparation processes during synthesis. Therefore, many researchers are committed to improving the synthesis methods, optimizing doping elements, and exploring new synthesis routes to enhance the luminous performance and application effects of sulfide phosphors.

[0003] Patent Publication No. CN112892563A discloses an F-doped ZnCdS solid solution photocatalytic material, its preparation method and application. First, nano-flower-shaped ZnCdS is obtained through a hydrothermal synthesis method, and then F-doped ZnCdS is obtained through a second hydrothermal method. However, this ZnCdS is used as a catalyst for photocatalysis and does not involve the concept of excitation / emission wavelengths. Summary of the Invention

[0004] The purpose of the present invention is to overcome the defects of the above-mentioned existing technologies and provide a purple-light-excited orange phosphor, its preparation method and application, which have higher luminous efficiency, better color purity, and stronger environmental adaptability, so that the prepared orange phosphor has strong emission intensity and has the advantage of stable physical and chemical properties, and can be widely matched with commercial purple LED chips.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] One of the technical solutions of the present invention is to provide a purple-light-excited orange phosphor, and the chemical formula of the orange phosphor is Zn4CdS5.

[0007] Further, the emission band of the orange phosphor is 450 - 800 nm.

[0008] Furthermore, the central wavelength of the emission band of the orange phosphor is 650 - 660 nm.

[0009] Further, the excitation wavelength of the orange phosphor is 200 - 600 nm, which is in the region from purple light to red light.

[0010] The second technical solution of the present invention lies in providing a preparation method of an orange phosphor excited by ultraviolet light. A Zn compound and a Cd compound are ground and mixed evenly, sealed in a vacuum quartz tube and calcined, and the orange phosphor is obtained after cooling, wherein the Zn compound and the Cd compound contain S element.

[0011] Further, the Zn compound includes a Zn sulfide;

[0012] The Cd compound includes a Cd sulfide.

[0013] Further, the Zn compound includes ZnS;

[0014] The Cd compound includes CdS.

[0015] Further, the mass ratio of the Zn compound to the Cd compound is (3.2 - 5.5):(0.2 - 1.8).

[0016] Still further, the mass ratio of the Zn compound to the Cd compound is (4 - 4.7):(0.3 - 1.1).

[0017] Further, the calcination temperature in the quartz tube is 300 - 1000 °C.

[0018] Still further, the calcination is carried out in stages. The first-stage calcination temperature is 300 - 500 °C, the second-stage calcination temperature is 750 - 1000 °C, and the third-stage calcination temperature is 450 - 550 °C.

[0019] Still further, the specific process of the staged calcination is as follows:

[0020] First-stage calcination: Heat up to 300 - 500 °C within 600 min and keep warm for 800 - 1200 min;

[0021] Second-stage calcination: Heat up to 750 - 1000 °C within 200 - 400 min and keep warm for 200 - 400 min;

[0022] Third-stage calcination: Cool down to 450 - 550 °C after 300 - 500 min and keep warm for 150 - 250 min.

[0023] Still further, the heating rate of the first-stage calcination is 0.5 - 1 °C / min, the heating rate of the second-stage calcination is 1.5 - 2 °C / min, and the cooling rate of the third-stage calcination is 0.2 - 0.5 °C / min.

[0024] Further, the grinding time is 20 - 50 min.

[0025] The third technical solution of the present invention lies in providing an application of a purple light-excited orange phosphor in the field of lighting devices, wherein the orange phosphor is assembled with a purple light chip to form an infrared detection device.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] (1) The phosphor of the present invention can emit orange light with a spectral range covering 450 - 800 nm and a central wavelength located at 650 - 660 nm under purple light excitation, and has not been reported before.

[0028] (2) Compared with the prior art, the orange phosphor of the present invention is a sulfur-based self-luminous phosphor, which has the advantages of stable physical and chemical properties and high cost performance. At the same time, the orange phosphor can be prepared by a conventional solid-phase reaction method, has the characteristics of simple preparation process and is conducive to industrial production, and has good performance, and can be a candidate material for wide application.

[0029] (3) The purple light-excited orange phosphor of the present invention can be well matched with existing commercial purple light LED chips, and is suitable for applications such as purple light chip white light LEDs, purple light chip solar-like LEDs, and purple light chip full-spectrum LEDs.

[0030] (4) Since the orange phosphor of the present invention is self-luminous, problems such as limited luminous efficiency caused by concentration quenching are avoided. Description of the Drawings

[0031] Figure 1 It is the photoinduced excitation-emission spectrum diagram of Example 1;

[0032] Figure 2 It is the photoluminescence spectra of Examples 1 - 3;

[0033] Figure 3 It is the XRD pattern of Example 1. Detailed Embodiments

[0034] The present invention will be described in detail below with reference to the drawings and specific embodiments. This embodiment is implemented on the premise of the technical solution of the present invention, and gives detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following embodiments. Based on the given embodiments, all other embodiments obtained by those of ordinary skill in the art without creative efforts fall within the scope of protection of this application. Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art.

[0035] Example 1

[0036] 1. Select ZnS and CdS as starting materials with a mass ratio of 4.6788:0.4334. Weigh the two raw materials separately and control the total mass of the raw material mixture to be about 5 g of the mixed raw materials.

[0037] 2. Place the above raw material mixture in an agate mortar and grind it for about 30 minutes. After the materials are mixed evenly, load the mixture into a quartz tube and vacuum seal it. Then, place the quartz tube containing the raw materials in a muffle furnace and heat it to 400 °C at a heating rate of about 0.6 °C / min within about 600 min, and keep it warm for about 1000 minutes; then heat it to 750 °C at a heating rate of about 1.7 °C / min within about 300 minutes, and then keep it warm for about 360 minutes; cool it to 500 °C at a cooling rate of about 0.63 °C / min within about 400 minutes; finally, cool it to room temperature with the furnace to obtain the target product Zn4CdS5.

[0038] 3. Use a fluorescence spectrometer (HITACHI F-7000) to test the spectral properties of the phosphor in this system, such as Figure 1 (The left curve is the excitation spectrum and the right curve is the emission spectrum) and Figure 2 as shown. The results show that the phosphor in this system has a relatively wide excitation band, covering the ultraviolet to green light region (300 - 550 nm), with a peak located near 384 nm and a relatively high spectral peak, indicating that it can be effectively excited by ultraviolet and violet chips and matches well with n-UV LED chips. Under the excitation of a 400 nm violet light source, the phosphor emits bright orange light, and the emission spectrum consists of a relatively wide emission band (450 - 800 nm), with a peak located at 652 nm. The prepared orange phosphor has a high response to violet light with strong emission intensity and has the advantage of stable physical and chemical properties, and can widely match commercial near-ultraviolet LED chips. As Figure 3 , the XRD pattern of the sample matches well with the Zn4CdS5 standard card, so it can be determined that the synthesized sample is Zn4CdS5 rather than other substances.

[0039] Example 2

[0040] 1. Select ZnS and CdS as starting materials with a mass ratio of 4.6788:0.4334. Weigh the two raw materials separately and control the total mass of the raw material mixture to be about 5 g of the mixed raw materials.

[0041] 2. Place the above raw material mixture in an agate mortar and grind it for 30 minutes. After the materials are evenly mixed, load the mixture into a quartz tube and vacuum-seal it. Then, place the quartz tube containing the raw materials in a muffle furnace. Heat it to 400 °C at a heating rate of about 0.6 °C / min within about 600 min, and keep it at this temperature for about 1000 minutes. Subsequently, heat it to 800 °C at a heating rate of about 1.7 °C / min within about 300 minutes, and then keep it at this temperature for about 360 minutes. Then, cool it to 500 °C at a cooling rate of about 0.63 °C / min within about 400 minutes. Finally, cool it to room temperature with the furnace to obtain the target product.

[0042] 3. Use a fluorescence spectrometer (HITACHI F-7000) to test the spectral properties of the phosphor in this system, such as Figure 2 . The results show that the phosphor in this system has a relatively wide excitation band, covering the ultraviolet to green light region (300 - 550 nm), with a peak located near 383 nm. The spectral peak is relatively high, indicating that it can be effectively excited by ultraviolet and violet chips and matches well with n-UV LED chips. Under the excitation of a 400-nm violet light source, this phosphor emits bright orange light, and its emission spectrum consists of a relatively wide emission band (450 - 800 nm), with a peak located at 655 nm. The prepared orange phosphor has a high response to violet light with strong emission intensity and has the advantage of stable physical and chemical properties, and can be widely matched with commercial near-ultraviolet LED chips.

[0043] Example 3

[0044] 1. Select ZnS and CdS as starting materials, with a mass ratio of 4.6788:0.4334. Weigh the two raw materials separately and control the total mass of the raw material mixture to be about 5 g.

[0045] 2. Place the above raw material mixture in an agate mortar and grind it for 30 minutes. After the materials are evenly mixed, load the mixture into a quartz tube and vacuum-seal it. Then, place the quartz tube containing the raw materials in a muffle furnace. Heat it to 400 °C at a heating rate of 0.6 °C / min within 600 min, and keep it at this temperature for 1000 minutes. Subsequently, heat it to 50 °C at a heating rate of 1.7 °C / min within 300 minutes, and then keep it at this temperature for 300 minutes. Then, cool it to 500 °C at a cooling rate of 0.63 °C / min within 400 minutes. Finally, cool it to room temperature with the furnace to obtain the target product.

[0046] 3. Use a fluorescence spectrometer (HITACHI F-7000) to test the spectral properties of the phosphor in this system, such as Figure 2As shown in the figure. The results show that the phosphor of this system has a wide excitation band, covering the ultraviolet to green light region (300 - 550 nm), with a peak located near 385 nm. The spectral peak is relatively high, indicating that it can be effectively excited by ultraviolet and violet chips and matches well with n-UV LED chips. Under the excitation of a 400-nm violet light source, the phosphor emits bright orange light, and the emission spectrum consists of a relatively wide emission band (450 - 800 nm), with a peak located at 651 nm. The prepared orange phosphor has a high response to violet light with strong emission intensity and has the advantage of stable physical and chemical properties, and can be widely matched with commercial near-ultraviolet LED chips.

[0047] Comparative Case 1

[0048] ZnS in Example 1 was selected and its spectral properties were tested using a fluorescence spectrometer (HITACHI F-7000), and it was found that it did not emit light.

[0049] Comparative Case 2

[0050] CdS in Example 1 was selected and its spectral properties were tested using a fluorescence spectrometer (HITACHI F-7000), and it was found that it did not emit light.

[0051] Comparative Case 3

[0052] ZnS:Cd was synthesized with reference to (Wang W, Germanenko I, El-Shall M S. Room-temperature synthesis and characterization of nanocrystalline CdS, ZnS, and CdxZn1-xS[J]. Chemistry of Materials, 2002, 14(7): 3028 - 3033). The preparation process is as follows:

[0053] An appropriate amount of sulfur powder (CAS No. 7704-34-9, powder, 99.98% trace metals basis, Shanghai Macklin Biochemical Co., Ltd.) was added to a flask containing 50 milliliters of tetrahydrofuran (THF). After magnetic stirring for 5 minutes, the mixture became a colorless transparent solution. Stoichiometric amounts of CdCl2 and ZnCl2 powders were added to the flask, and a white suspension was formed after stirring. After adding potassium borohydride, the suspension turned light yellow. After stirring for 12 hours, a yellow precipitate was formed. After filtration, it was washed several times with carbon disulfide, ethanol, and distilled water to remove possible impurities such as potassium chloride and excess sulfur. Then the precipitate was dried at room temperature for 12 hours to obtain ZnS:Cd.

[0054] Using a fluorescence spectrometer (HITACHI F-7000), the emission wavelength was tested between 400 - 700 nm, which was completely different from the spectrum of Zn4CdS5 in Example 1.

[0055] Comparative Example 4

[0056] Compared with Example 1, most of them were the same, except that ZnS and CdS were selected as starting materials, and their mass ratio was 0.9775:1.4447. The two raw materials were weighed separately, and the total mass of the raw material mixture was controlled to be about 5 g. ZnCdS2 was synthesized, and a fluorescence spectrometer (HITACHI F-7000) was used to test the spectral properties. It was found that the optimal excitation / emission wavelengths of the two spectra were completely different from those of Zn4CdS5 in Example 1.

[0057] Comparative Example 5

[0058] Compared with Example 1, most of them were the same, except that the mixed raw materials were heated in a muffle furnace at a heating rate of 5 °C / h to 750 °C, held for 1360 minutes, cooled at a cooling rate of 5 °C to 500 °C after 400 minutes, and finally cooled to room temperature with the furnace. After measurement, the XRD pattern showed that the starting materials were ZnS and CdS. And the maximum temperature that the quartz tube could withstand was 1000 °C, and the sulfide would be oxidized in an air environment, so the target product Zn4CdS5 could not be synthesized. At low temperatures (<300 °C), the melting point of the sulfide was not reached, and the system did not react, so the target product Zn4CdS5 could not be synthesized.

[0059] Comparative Example 6

[0060] Compared with Example 1, most of them were the same, except that CdS was replaced by CdCl2, and Zn4CdS5 could not be synthesized.

[0061] Comparative Example 7

[0062] Compared with Example 1, most of them were the same, except that ZnS was replaced by ZnNO3, and Zn4CdS5 could not be synthesized.

[0063] Table 1 shows the relevant preparation parameters of Examples 1 - 3 and Comparative Examples 3 and 4.

[0064] Table 1 Relevant preparation parameters of Examples 1 - 3 and Comparative Examples 3 and 4

[0065]

[0066] As can be seen from the above table, the Zn4CdS5 phosphor can emit orange light with a spectral range covering 450 - 800 nm and a central wavelength located at 650 - 660 nm under ultraviolet excitation, showing a high response to ultraviolet light with strong emission intensity. When excited by a 400-nm ultraviolet light source, the phosphor emits strong orange light and has stable physical and chemical properties.

[0067] Since no activator is required for luminescence, this material avoids the problem of reduced luminescence efficiency caused by concentration quenching. In addition, it also solves the problem of non-radiative transition caused by the too-close distance between luminescence centers, and thus has a relatively high color purity.

[0068] Although the present invention has been described in detail above with general descriptions, specific embodiments and experiments, some modifications or improvements can be made to it based on the present invention, which are obvious to those skilled in the art. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of the present invention claimed.

Claims

1. An orange phosphor excited by ultraviolet light, characterized in that, The chemical formula of the orange phosphor is Zn4CdS5.

2. The orange phosphor excited by ultraviolet light according to claim 1, characterized in that, The emission band of the orange phosphor is 450 - 800 nm.

3. The orange phosphor excited by ultraviolet light according to claim 1, wherein, The excitation wavelength of the orange phosphor is 200 - 600 nm, located in the region from violet light to red light.

4. The preparation method of an orange phosphor excited by ultraviolet light according to any one of claims 1 to 3, characterized in that, A Zn-containing compound and a Cd-containing compound are ground and mixed evenly, sealed in a vacuum quartz tube and calcined, and the orange phosphor is obtained after cooling. The Zn-containing compound and the Cd-containing compound contain S element.

5. The preparation method of an orange phosphor excited by ultraviolet light according to claim 4, characterized in that, The Zn-containing compound includes a Zn sulfide. The Cd-containing compound includes a Cd sulfide.

6. The preparation method of an orange phosphor excited by ultraviolet light according to claim 4, characterized in that, The Zn-containing compound includes ZnS. The Cd-containing compound includes CdS.

7. The preparation method of an orange phosphor excited by ultraviolet light according to claim 4, characterized in that, The mass ratio of the Zn-containing compound to the Cd-containing compound is (3.2 - 5.5):(0.2 - 1.8).

8. The preparation method of an orange phosphor excited by ultraviolet light according to claim 4, characterized in that, The calcination temperature in the quartz tube is 300 - 1000 °C.

9. The preparation method of an orange phosphor excited by ultraviolet light according to claim 8, characterized in that, The calcination is carried out in stages. The first-stage calcination temperature is 300 - 500 °C, the second-stage calcination temperature is 750 - 1000 °C, and the third-stage calcination temperature is 450 - 550 °C.

10. Application of an orange phosphor excited by ultraviolet light in the field of lighting devices according to any one of claims 1 to 3, characterized in that, The orange phosphor is assembled with a violet chip to form an LED device.

Citation Information

Patent Citations

  • Preparation method of multi-morphology Zn-Cd-S semiconductor nano composite material based on one-step controllable synthesis

    CN102502787A

  • Making method of white light LED light source

    CN1485931A